Effect of starch-based supplementation level combined with oil on intake, performance, and methane emissions of growing Nellore bulls on pasture - José Neto, A. [UNESP]; Messana, J. D. [UNESP]; Ribeiro, A. F. [UNESP]; Vito, E. S. [UNESP]; Rossi, L. G. [UNESP]; Berchielli, Telma Teresinha [UNESP] (Amer Soc Animal Science, 2015)
Intake of tropical grass forages alone is generally insufficient to avoid nutrition imbalances and reduced animal performance; therefore, supplementation is often recommended. The hypothesis of the present study is that when combined with fat, soybean hulls (SH) could replace corn as a source of energy, reducing methane production without affecting animal performance. This study evaluated the effects of starch-based supplementation level combined with oil on intake, digestibility, performance, and methane emissions of growing Nellore bulls (n = 44; initial BW = 250.69 +/- 27 kg) fed Brachiaria brizantha cv. Xaraes during the rainy season. There were no interactions between starch level and oil supplementation with regard to intake of DM (P = 0.67), forage DM (P = 0.55), supplement DM (P = 0.14), OM (P = 0.66), CP (P = 0.74), NDF (P = 0.50), ether extract (EE; P = 0.47), and GE (P = 0.68). The intake of EE was greater for animals supplemented with oil than those fed supplements without oil (P < 0.01). There were no interactions between starch level and oil supplementation on digestibility of DM (P = 0.18), OM (P = 0.11), NDF (P = 0.42), and EE (P = 0.14). Moreover, there was interaction between starch and oil supplementation on GE (P < 0.01). Independent of starch level used, the addition of oil decreased the digestibility of OM (P = 0.04) and NDF (P = 0.03). There were no main effects of starch level, oil, or interaction between starch and oil for initial BW (P = 0.10), final BW (P = 0.94), ADG (P = 0.40), feed efficiency (P = 0.37), and carcass gain (P = 0.38). There was no interaction between starch-based supplementation level and oil on methane emissions when expressed in grams per day (P = 0.77), kilograms per year (P = 0.77), grams per kilogram DMI (P = 0.53), and grams per kilogram carcass gain (P = 0.31). There was, however, an interaction (P = 0.04) between starch level and oil on methane emissions when corrected for NDF intake. Additionally, oil decreased enteric methane emission for intake of GE (P = 0.04) and EE (P < 0.01) of animals fed with starch level. Soybean hulls have an estimated feeding value similar to that of corn. The use of oil supplementation may be effective to reduce enteric methane emission of Nellore bulls raised on pasture.
Keywords: Corn; Greenhouse gases; Ruminant; Soybean hulls; Tropical grass